دور تطبيق المواصفة ISO9001:2015 في تخفيض الأخطاء البشرية وحالات عدم المطابقة دراسة حالة في مديرية المهن والرخص في محافظة دمشق - Balkhi, Rateb Mohamad; Sammour, Amer Mohamad (Latakia University Journal - Economic and Legal Sciences Series, 2019)
دور تطبيق المواصفة ISO9001:2015 في تخفيض الأخطاء البشرية وحالات عدم المطابقة دراسة حالة في مديرية المهن والرخص في محافظة دمشق راتب محمد البلخي عامر محمد سمور يهدف هذا البحث إلى دراسة دور تطبيق المواصفة القياسية 9001:2015ISO في تخفيض الأخطاء البشرية وحالات عدم المطابقة، وقد طبقت هذه الدراسة على مديرية المهن والرخص في محافظة دمشق. وهي مديرية طبقت نظام إدارة الجودة وفق المواصفة القياسية 9001:2015ISO. وتم استخدام المنهج الوصفي التحليلي المتضمن جمع البيانات المتعلقة بمتغيرات الدراسة وتحليلها. تم التوصل إلى نتائج عديدة أهمها: إن تطبيق المواصفة القياسية يؤدي إلى تخفيض الأخطاء البشرية، والأخطاء الإدارية وحالات عدم المطابقة. كما تم وضع عدد من المقترحات أهمها: ضرورة تطبيق متطلبات المواصفة في باقي مديريات المهن والرخص والقطاع الحكومي الخدمي في الجهات التي لم تقم بتطبيق المتطلبات بعد. This study aims to study the role of applying ISO 9001: 2015 in reducing human errors and cases of nonconformity. This study was applied to the Directorate of Professions and Licenses in Damascus Governorate. The Directorate has applied the quality management system in accordance with the standard ISO 9001: 2015. A descriptive analytical approach was used to collect and analyze data on study variables. Several results have been reached: The application of the standard reduces human errors, administrative errors and nonconformity. A number of proposals were also put forward: The necessity of applying the requirements of the standard in the other departments of the professions and licenses and the government service sector in the entities that have not yet applied the requirements.